2011
DOI: 10.1080/00207594.2010.503762
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and production mode on the bilingual performance of Turkish learners of English in a serial recall task

Abstract: The cognitive resources available to the working memory system are finite. Under conditions of cognitive overload, a compromise may need to be made between the demands of storage and processing. Research suggests that the cognitive cost of partially automated transcription processes adversely affects written language production in children. Thus, children may be expected to perform the same task better orally than in writing. In order to determine whether this is the case in a Turkish context, three samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Accordingly, participants generally took longer to answer emotional compared to neutral questions. Our data also showed that participants took longer to answer questions in the foreign compared to their native language, which is in accordance with the idea that processing of a foreign language requires more cognitive resources (Akca & Elkilic, 2011;Ardila, 2003;Service et al, 2002). We also found that in general, lying took longer than truth telling (Suchotzki et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, participants generally took longer to answer emotional compared to neutral questions. Our data also showed that participants took longer to answer questions in the foreign compared to their native language, which is in accordance with the idea that processing of a foreign language requires more cognitive resources (Akca & Elkilic, 2011;Ardila, 2003;Service et al, 2002). We also found that in general, lying took longer than truth telling (Suchotzki et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Although this is a limiting factor of the current studies, we felt the benefits to external validity of using a more diverse set of targets was worthwhile. Also potentially problematic was the lack of a manipulation check on cognitive load; it was presumed from previous research (e.g., Akca & Elkilic, ; Ardila, ; Service et al, ) that non‐native speakers would experience higher levels of load than native speakers; however, this was not measured directly in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…When lying in a second language, the deceiver is simultaneously faced with the challenging task of lying (Vrij, Fisher, Mann, & Leal, , ) and the resource‐intensive task of speaking a second language (e.g., Akca & Elkilic, ; Ardila, ; Service, Simola, Metsanheimo, & Maury, ). Although the relatively difficult task of speaking a second language remains for truth tellers, because honesty is not particularly cognitively demanding, they may be better able to cope with the cognitive requirements of using a second language.…”
Section: Detecting Deception In Non‐native English Speakersmentioning
confidence: 99%
“…Consequently, liars have fewer cognitive resources left over to cope when cognitive demand is further raised in an interview. Cognitive demand is further raised by requesting interviewees to communicate in a foreign language (Akca & Elkilic, ; Evans et al ., ). Such a request should thus affect liars more than truth tellers, with verbal cues to deceit likely to occur.…”
Section: Verbal Cues To Deceitmentioning
confidence: 99%